Dimensionality in Language Learners’ Personal Epistemologies - Nikitina, Larisa; Furuoka, Fumitaka (Eskisehir Osmangazi University, 2018)
This study aimed to examine dimensionality in language learners' epistemic beliefs. To achieve this, a survey was conducted using a newly-developed research instrument-"Language Learners' Epistemic Beliefs" (LLEB) questionnaire. Based on a review of literature, it was proposed that language learners' epistemic beliefs would cluster in three dimensions: (1) the nature of knowledge, (2) the authority to knowledge, and (3) the process of gaining linguistic knowledge. The data for this study were collected from 23 students majoring in languages and linguistics in a large Malaysian public university. Exploratory factor analysis of the data uncovered five latent dimensions in the students' personal epistemologies. They were named "Authority to knowledge", "Nature of knowledge", "Concentration", "Hard work", and "Effort". These findings did not refute the proposed conceptualization of language learners' personal epistemologies as measured by the LLEB questionnaire. However, they revealed that discipline-specific epistemologies may have more complex structures. For example, an important finding was that the beliefs pertaining to the process of learning, which are considered as 'peripheral' to the function of personal epistemologies by some researchers, occupied a distinct and prominent position in the language learners' personal epistemologies.